Proteome profiling of embryo chick retina - Souchelnytskyi Nazariy (Proteome Science, 2008)
Abstract Background Little is known regarding the molecular pathways that underlie the process of retinal development. The purpose of this study was to identify proteins which may be involved in development of retina. We used a proteomics-based approach to identify proteins that are up- or down-regulated during the development of the embryo chick retina. Results Two-dimensional gel electrophoresis was performed with the retina of embryo chicken, which was obtained from embryos of day 7 (ED7) and of day 11 (ED11). The protein spots showing significant differences were selected for identification by MALDI mass spectrometry. Thirteen proteins were differentially expressed; seven proteins were up-regulated in embryo retina of chicken at ED 11 and six proteins were down-regulated. Significant proteins were also evaluated in embryo day 15 (ED15). Some of identified proteins were known to regulate cell proliferation, cell death, transport, metabolism, organization and extracellular matrix, and others also included novel proteins. Conclusion We identified thirteen proteins which differentially expressed in embryonal retina of chicken at day 7, as compared to the retina of embryo of day 11. They were various regulatory proteins for cellular signaling.